The Use of Artificial Intelligence with Mechanisms in Robots in the Linkage of the Manufacturing Industry: Systematic Literature Review - Dwilaga, Armando Tirta (Fakultas Sains dan Teknologi Universitas Islam Negeri Sultan Syarif Kasim Riau, 2023)
This paper aims to provide an overview of the literature by looking at the use of artificial intelligence with robotic mechanisms in the manufacturing industry. The PRISMA method approach is used in a modified framework to take into account the inclusion and exclusion criteria, one of the bases for selection is the basic understanding of artificial intelligence technology obtained from the Scopus index database only for 2020, 2021, and 2022. The results were from 1178 articles to 481 contiguous articles until the selection of 36 articles. The journal description used as the most common reference of Frontiers in Robotics and AI was used to identify these papers in more depth, the most common journal publisher was Frontiers Media S.A, Italy was the most common country of origin found, and quantitative research was the most common methodology used. Research in 2020, 2021, and even 2022 is still a fraction of what is now being discussed, but the last three years have seen significant growth in discussions on this topic, creating tremendous opportunities for additional studies.